ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELOLAAN KEUANGAN INSTITUT AGAMA ISLAM NEGERI (IAIN) AMBON - Fadila Patty (Soso-Q : Jurnal Manajemen, 2019)
This study aims to find out partially the effect of transparency, value for money, and income on financial management of IAIN Ambon. And to find out transparency, value for money, and income jointly affect the financial management of IAIN Ambon. The population in this study amounted to 60 people consisting of all Echelon II, III and IV officials and JFUs in particular the education sector as well as the entire Chair and Secretary of the departments at IAIN Ambon. With a Purposive Sampling technique, a sample of 30 people was obtained. The data analysis technique used is path analysis, for hypothesis testing using the T test, which is to find out the effect partially between the independent variable and the dependent variable, and the F test to know the effect simultaneously of all independent variables on the dependent variable. The results of this study indicate that: 1) There is no positive and significant effect between transparency and financial management in Ambon IAIN. 2) There is a positive and significant effect between Value for Money and Ambon IAIN financial management. 3) There is a positive and significant effect between Revenue and Ambon IAIN financial management. 4) There is a positive and significant effect together between Transparency, Value for Money, and Revenue with the financial management of IAIN Ambon. Keywords: Transparency, Value for Money, Income, and Financial Management